ANALISIS KOMPARASI KAJIAN TERJEMAHAN INGGRIS-ARAB DAN INGGRIS-INDONESIA PADA LIRIK LAGU BTS - Rahmawati, Khoirunnisa; Malik, Abdul (Adabiyyāt: Jurnal Bahasa dan Sastra, 2023)
Subtitles on YouTube are automatically machine-translated and sometimes the translations are difficult to understand. One of the applications is done on BTS song lyrics. The purpose of this study is to compare the application of techniques as well as the tendency of English-Arabic and English-Indonesian translation methods and ideologies in BTS song lyrics. This research is a descriptive qualitative research. The translation theories underlying this research are translation techniques, methods, and ideologies. The data in this study are clauses or sentences in the lyrics of BTS songs and their translations in Arabic and Indonesian. The data collection technique was done by listening and noting. The data were analyzed by combining two analysis models, namely interactive (Miles and Huberman) and ethnographic (Spradley) models. The results of this study show that the dominant application of translation techniques in English-Arabic translation is the established equivalent technique, while in English-Indonesian translation it is the literal technique. Meanwhile, the English-Arabic translation method is target language-oriented, while the English-Indonesian translation method is source language-oriented. This affects the domestication ideology orientation in English-Arabic translation and the foreignization ideology orientation in English-Indonesian translation.